2017
DOI: 10.1063/1.4985224
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in two-dimensional non-collinear antiferromagnetic semiconductor Cr0.68Se

Abstract: Cr0.68Se single crystals with two-dimensional (2D) character have been grown, and the Cr0.68Se is dominated by the skew-scattering mechanism. Our results may be helpful for exploring the potential application of these kind of 2D AFM semiconductors.*Corresponding authors: xluo@issp.ac.cn and ypsun@issp.ac.cn

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…However, the skew scattering follows a different relation ρ A xy ∝ ρ xx . It has been demonstrated that the AHE in 2D Cr 0.68 Se, with a Néel temperature around 42 K, is dominated by the skew-scattering mechanism rather than the side-jump or KL mechanism [43]. The temperature-dependent transversal resistance ρ xy of Cr 0.68 Se is shown in Figure 4(b).…”
Section: Anomalous Hall Effect Anomalous Hall Effect (Ahe)mentioning
confidence: 98%
See 2 more Smart Citations
“…However, the skew scattering follows a different relation ρ A xy ∝ ρ xx . It has been demonstrated that the AHE in 2D Cr 0.68 Se, with a Néel temperature around 42 K, is dominated by the skew-scattering mechanism rather than the side-jump or KL mechanism [43]. The temperature-dependent transversal resistance ρ xy of Cr 0.68 Se is shown in Figure 4(b).…”
Section: Anomalous Hall Effect Anomalous Hall Effect (Ahe)mentioning
confidence: 98%
“…It is fundamentally different from the ordinary Hall effect (that only involves the orbital deflection of the carrier transport caused by the external magnetic field-induced Lorenz force) [42]. Basically, there are three basic mechanisms to induce AHE, as shown in Figure 4(a) [43]. The AHE can either be intrinsic or extrinsic.…”
Section: Anomalous Hall Effect Anomalous Hall Effect (Ahe)mentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Additionally, Cr n X (X = S, Se and Te; 0 < n < 1) possesses a number of binary compounds with different component ratios, which leads to a number of structural phases and physical properties. [35][36][37][38][39] The Cr n Se obtained thus far has mainly been in bulk state and few properties have been reported for its 2D structure. Besides, it is suspected that CrSe crystals have anomalous magnetic properties, but few works have been reported on CrSe, not to mention the synthesis of 2D CrSe crystals.…”
Section: Doi: 101002/adma201900056mentioning
confidence: 99%
“…3(b). In general, the Hall resistivity ρ xy in the ferromagnets is made up of two parts, [32][33][34][35]…”
Section: Resultsmentioning
confidence: 99%